Phytochemical characterization of Clitoria ternatea Linn biodirected for its potential against multiresistant microorganisms / Caracterização fitoquímica de Clitoria ternatea Linn biodirecionada pelo seu potencial contra micro-organismos multirresistentes - Maurício Santos de Melo; Mariane Carvalho Santos; João Gomes da Costa; Luana Luzia Santos Pires; Thiago José Matos Rocha; Aldenir Feitosa dos Santos (Universidade Estadual de Alagoas, 2018)
Challenges in treating infectious diseases are growing significantly, considering that the clinical efficacy of many antimicrobials has been threatened by the emergence of multiresistant pathogens. Clitoria ternatea, commonly known as Cunhã, has several medicinal properties, determined by empirical use. There are no reports in literature about inhibition of multiresistant bacteria by the antimicrobial activity of extracts of C. ternatea, therefore there is a need for additional studies to detect new therapeutic options against these microorganisms that cause serious infections. Thus, the aim of this work is to evaluate the antibacterial activity of C. ternatea crude extract and its partitions against clinical isolates of multiresistant bacteria responsible for nosocomial infection. The extracts were tested by broth microdilution method. Serial dilutions were performed to determine minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The extract and its partitions presented inhibitory activity of 100 μg/mL and 250 μg/mL against the Staphylococcus aureus MRSA, Klebsiella pneumoniae ESBL and Acinetobacter baumannii MBL samples, demonstrating action against gram-positive and gram-negative bacteria with different mechanisms of resistance. Phytochemical analysis showed phenolic compounds, flavonoids, alkaloids, saponins and tannins.